2019
DOI: 10.3390/ijerph16234695
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-Temporal Effects of PM2.5 on Health Burden: Evidence from China

Abstract: By collecting the panel data of 29 regions in China from 2008 to 2017, this study used the spatial Durbin model (SDM) to explore the spatial effect of PM2.5 exposure on the health burden of residents. The most obvious findings to emerge from this study are that: health burden and PM2.5 exposure are not randomly distributed over different regions in China, but have obvious spatial correlation and spatial clustering characteristics. The maximum PM2.5 concentrations have a significant positive effect on outpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 55 publications
2
19
0
Order By: Relevance
“…Many countries have opted for cleaner and environmentally friendly energy production technologies to cope with the horrors of climate change. Although they constitute only a small part of total global primary energy, renewable energy sources generate less CO2 emissions than non-renewable sources, which constitute a significant share of total global primary energy (Zeng et al, 2019). In Cameroon, the consumption of renewable energies during the period 2000-2017 represents between 78% and 84.5% of global energy consumption (IEA et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Many countries have opted for cleaner and environmentally friendly energy production technologies to cope with the horrors of climate change. Although they constitute only a small part of total global primary energy, renewable energy sources generate less CO2 emissions than non-renewable sources, which constitute a significant share of total global primary energy (Zeng et al, 2019). In Cameroon, the consumption of renewable energies during the period 2000-2017 represents between 78% and 84.5% of global energy consumption (IEA et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Where, d ij is the road distance between region i and region j. However, the above two spatial weight matrixes only reflect the geographical relationship between regions, but they cannot reflect the influence of other factors (27). Hence, we also construct the spatial economic weight matrix W3 as follows:…”
Section: Spatial Autocorrelation Testmentioning
confidence: 99%
“…Song conducted research to estimate the health burden attributable to ambient PM2.5 across China by using the exposure-response model [ 11 ]. Zeng applied spatial autocorrelation analysis, hot spot analysis, and spatial empirical analysis to explore the spatial distribution of PM2.5 and described its relationship with healthcare services [ 12 ]. Wang revealed that water pollution was negatively associated with health outcomes by using a random-effects model, a random-effects logit model, and a mediator model [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution could spread over adjacent provinces with no regard for political boundaries [ 28 ]; water pollution upstream could cause destructive effects on downstream regions [ 29 ]; solid waste can contaminate soil without being limited by space [ 30 ]. To an extent, some studies have analyzed the spill-over effects of air pollution [ 12 ]; however, these spill-over effects have still not been fully considered, such as spill-overs due to water pollution and solid-waste pollution. Apart from that, specifically, there has been no detailed discussion about the relationship between outpatient services, inpatient services, and environmental pollution.…”
Section: Introductionmentioning
confidence: 99%